ACTIVITY BASED COSTING SYSTEM AND ITS ROLE IN DECISION MAKING. A CASE STUDY OF CEMENT COMPANIES IN KURDISTAN REGION OF IRAQ - Omar, Raqeeb; Hasan, Nawzad (International Journal of Psychosocial Rehabilitation, 2020)
The study dwells on the analysis of activity based costing system and its role in decision making in relation to Kurdistan Region of Iraq. This stems from propositions made that traditional costing tends to yields astonishing results on the condition that there is efficient accounting systems and there are no complexities that can hinder accurate accounting procedures. Results from the study were based on survey120 respondents from Bazian Cement Company and the results showed activity based costing elements of cost management, performance and quality management are positively related to decision making. Conclusions were thus made that activity based costing plays a vital role in the decision making of firms especially that of Bazian Cement Company.